2019
DOI: 10.1186/s12984-019-0580-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing general spatial skills of young visually impaired people with a programmable distance discrimination training: a case control study

Abstract: Background The estimation of relative distance is a perceptual task used extensively in everyday life. This important skill suffers from biases that may be more pronounced when estimation is based on haptics. This is especially true for the blind and visually impaired, for which haptic estimation of distances is paramount but not systematically trained. We investigated whether a programmable tactile display, used autonomously, can improve distance discrimination ability in blind and severely visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In line with this, Hill et al [19] found that BLV individuals who utilized spatial skills, such as object-to-object relationships or perimeter/gridline patterns, were able to effectively explore a new space and locate objects. One error seen in tactile interpretation, which was identified in a study by Leo et al [13], was the overestimation of short lengths and the underestimation of long lengths.…”
Section: Strategies and Errors In Tactile Interpretationmentioning
confidence: 99%
See 4 more Smart Citations
“…In line with this, Hill et al [19] found that BLV individuals who utilized spatial skills, such as object-to-object relationships or perimeter/gridline patterns, were able to effectively explore a new space and locate objects. One error seen in tactile interpretation, which was identified in a study by Leo et al [13], was the overestimation of short lengths and the underestimation of long lengths.…”
Section: Strategies and Errors In Tactile Interpretationmentioning
confidence: 99%
“…Spatial skills have been identified as factors that contribute to retention rates and improved grade and course performance in STEM fields [10]- [13]. Wai et al discussed the consistency of heightened spatial skills in those who excelled in STEM domains but recognized that spatial ability is often overshadowed by mathematical or verbal skills when predicting success in STEM fields [3].…”
Section: Benefits Of Spatial Abilitymentioning
confidence: 99%
See 3 more Smart Citations